Неоднородность пластического течения биметаллического материала - Баранникова С. А. Светлана; Бочкарёва А. В. Анна Валентиновна; Зуев Л. Б. Лев Борисович; Ли Ю. В. Юлия Владимировна (2016, 2016)
Заглавие с экрана